The Effectiveness of the Teacher Professional Education Program in Improving Pedagogical and Professional Competence in the Digital Era - Saifullah; Suleha; Yusmah; Nuraini K; Muhammad Hanafi; Jusrianto; Nurlia Arsyad (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to evaluate the effectiveness of the Teacher Professional Education Program (PPG) in improving the pedagogical and professional competence of teachers in the digital era. With the rapid advancement of technology, demands for educational quality and teacher competence are increasing. The PPG program, as a means to enhance teacher quality in Indonesia, is expected to contribute significantly to the development of pedagogical competence and teacher professionalism in addressing the challenges of digital education. This research employs a quantitative survey approach involving teachers who have participated in the PPG program across several regions. The results indicate a significant improvement in participants' pedagogical competence, including understanding technology-based learning approaches and managing digital classrooms. However, challenges remain in the application of technology in daily teaching, particularly regarding limited access and adequate training. In conclusion, the PPG program has proven effective in enhancing pedagogical and professional competence, though improvements in modules and intensive training are needed to meet the growing demands of digital learning.